2021
DOI: 10.1088/1742-6596/1825/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Sediment and Crustal Structure Beneath East Kalimantan and East Java, Indonesia From Receiver Function

Abstract: We investigate the sediment and Earth’s crustal structure beneath the East Kalimantan and East Java by modelling the stacked receiver function from six seismic broadband stations belong to the Meteorology, Climatology and Geophysics Agency of Indonesia (BMKG). The calculation of receiver functions from 60 teleseismic earthquake events using iterative time-domain deconvolution method. Inversion result shows a significant variation in the sediment layer thickness from 1 km to 4 km beneath East Java. It is correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Other researchers performed the receiver function study in the island of Java where the thickness of the crust in the western part of the island was 25-37 km (Syuhada and Anggono, 2016; Anggono et al, 2020), in the central and east part of Java island about 25-39 km (Wölbern and Rümpker, 2016;Amukti et al, 2019). Recently, the receiver function study using limited number of stations in Borneo or Kalimantan Island was carried out by Bahri et al, 2021. They showed the evidence of thickening of the Earth's crust in cross-section from east Java to the north to Borneo Island.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers performed the receiver function study in the island of Java where the thickness of the crust in the western part of the island was 25-37 km (Syuhada and Anggono, 2016; Anggono et al, 2020), in the central and east part of Java island about 25-39 km (Wölbern and Rümpker, 2016;Amukti et al, 2019). Recently, the receiver function study using limited number of stations in Borneo or Kalimantan Island was carried out by Bahri et al, 2021. They showed the evidence of thickening of the Earth's crust in cross-section from east Java to the north to Borneo Island.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the sedimentary layer beneath a seismic station near the Tarakan Basin has a thickness of at least 2 km. However, the sedimentary thickness of around 0.55 km obtained for station SGKI is considerably less than that reported by previous seismological global and local studies [e.g., 13,14,21]. All these previous 1227 (2023) 012044 IOP Publishing doi:10.1088/1755-1315/1227/1/012044 4 studies suggest that the sedimentary layer with a thickness of more than 3 km covers the study area.…”
Section: Resultsmentioning
confidence: 59%
“…Research in East Java indicated sediment layer thickness of about 1-4 km with an average Vs velocity of approximately 2.40 km/s, and crustal layer with an average Vs velocity of 4.70 km/s at a depth of 20 -40 km. In East Borneo, the results revealed sediment thickness ranging from 5-10 km with an average Vs velocity of about 2.22 km/s, and the thickness of the Earth's crust varied between 34-50 km with an average Vs velocity of 4.48 km/s [11]. Furthermore, research in Borneo Island, divided into 5 zones -Sabah Zone, East Borneo Zone, Maratus Zone, Northwest Zone, and Southwest Zone, was conducted using nonlinear inversion methods.…”
Section: Introductionmentioning
confidence: 98%